(untitled) (Balneo and PRM Research Journal, 2024)
(1) Background: Flatfoot can alter the foot’s ability to uniformly distribute the body weight on the plantar areas, possibly leading to biomechanical imbalances in the entire body. Purpose of the study was to determine correlation between flatfoot and plantar pressure distribution in static condition. (2) Material and methods: The study included a group of 23 children with flat feet (7.43±0.58 years old), which analyzed the correlations between the Foot Posture Index 6 (FPI 6) values and the plantar pressure distribution values. The instruments used were the Foot Posture Index 6 (FPI 6-a quantitative anatomical assessment under static conditions) and the Podata (device for recording images in real time of the body weight distribution on the plantar support). (3) Results: The statistical results have indicated significant correlations of strong intensity between the flat foot and the plantar pressure distribution in the midfoot, but also that the flatfoot significantly influences the values of the plantar pressure distribution in the midfoot. (4) Conclusion: The data showed that flatfeet influence the values of the plantar pressure distribution in the mid-area of the sole.